2021
DOI: 10.1093/mnras/stab962
|View full text |Cite
|
Sign up to set email alerts
|

A revised SALT2 surface for fitting Type Ia supernova light curves

Abstract: We present a revised SALT2 surface (‘SALT2-2021’) for fitting the light curves of Type Ia supernovae (SNe Ia), which incorporates new measurements of zero-point calibration offsets and Milky Way extinction. The most notable change in the new surface occurs in the UV region. This new surface alters the distance measurements of SNe Ia, which can be used to investigate the nature of dark energy by probing the expansion history of the Universe. Using the revised SALT2 surface on public data from the first three ye… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 66 publications
0
24
0
Order By: Relevance
“…Throughout this work, we have repeatedly encountered a number of the steps of the analysis that have a large impact on various downstream codependent products of the analysis: new calibration (or MWEBV Maps/Color law) motivates new SALT2 training, which motivates new fitting of the SN parent populations, which motivates new bias corrections. The Pippin framework (Hinton & Brout 2020), used extensively in this work, was intentionally developed to automate and asynchronize this multistep type of analysis; however, it has yet to incorporate aspects such as the SALT2 retraining (Taylor et al 2021) or population fitting (Popovic et al 2021a). Likely, this framework will need to expand for future analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout this work, we have repeatedly encountered a number of the steps of the analysis that have a large impact on various downstream codependent products of the analysis: new calibration (or MWEBV Maps/Color law) motivates new SALT2 training, which motivates new fitting of the SN parent populations, which motivates new bias corrections. The Pippin framework (Hinton & Brout 2020), used extensively in this work, was intentionally developed to automate and asynchronize this multistep type of analysis; however, it has yet to incorporate aspects such as the SALT2 retraining (Taylor et al 2021) or population fitting (Popovic et al 2021a). Likely, this framework will need to expand for future analyses.…”
Section: Discussionmentioning
confidence: 99%
“…1. Baseline: We use the Fragilistic calibration solution and newly trained SALT2 model ("SALT2-B22") which was developed following the formalism of Guy et al (2010) and Taylor et al (2021). Systematics: For each of the 9 correlated realizations of Fragilistic zero-points discussed above (for Calibration) we simultaneously retrain the SALT2 model.…”
Section: Salt2 Modelmentioning
confidence: 99%
“…The Spectral Adaptive Light Curve Template-2 (SALT2; Guy et al 2007) is an improvement on the original SALT algorithm and has been recently revised (e.g. Taylor et al 2021).…”
Section: Supernova Light Curvesmentioning
confidence: 99%
“…For cosmological analyses with the SN Ia light-curve fitter SALT2 (Guy et al 2007(Guy et al , 2010, highly-reddened SN Ia are cut (−0.3 < 𝑐 < 0.3 with 𝑐 ∼ 𝐸 (𝐵 − 𝑉) − 0.1, e.g., Betoule et al 2014;Scolnic et al 2018;Brout et al 2022). These SNe Ia are not used in the training of the spectral model itself (Betoule et al 2014;Taylor et al 2021;Brout et al 2021), but it has not been shown that they cannot be used. In this analysis, we investigate these highly-reddened SNe Ia to constrain the evolution and variability of reddening.…”
Section: Introductionmentioning
confidence: 99%